2010
DOI: 10.1590/s1807-59322010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cushing’s Syndrome in Obese Patients

Abstract: OBJECTIVES:The aim of this study was to examine the frequency of Cushing’s syndrome (CS) in obese patients devoid of specific clinical symptoms of Cushing’s syndrome.METHODS:A total of 150 obese patients (129 female, 21 male; mean age 44.41 ± 13.34 yr; mean BMI 35.76 ± 7.13) were included in the study. As a first screening step, we measured 24-h urinary free cortisol (UFC). An overnight 1-mg dexamethasone suppression test was also performed on all patients. Urinary free cortisol levels above 100 μg/24 h were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
3
37
0
3
Order By: Relevance
“…Recent evidence has revealed a high prevalence of endogenous CS (1-5%) in certain patient populations, particularly in subjects with uncontrolled diabetes and/or hypertension, as well as osteoporosis [10][11][12]. Another current study reported a prevalence of CS of up to 9.3% in obese patients [13].…”
Section: Introductionmentioning
confidence: 58%
“…Recent evidence has revealed a high prevalence of endogenous CS (1-5%) in certain patient populations, particularly in subjects with uncontrolled diabetes and/or hypertension, as well as osteoporosis [10][11][12]. Another current study reported a prevalence of CS of up to 9.3% in obese patients [13].…”
Section: Introductionmentioning
confidence: 58%
“…It is possible that dogs with higher average bodyweight are more likely to be overweight and therefore these results may suggest that overweight/obesity may be associated with hyperadrenocorticism in dogs. Previous reports have also suggested that dogs with a higher body condition score were at higher risk of hyperadrenocorticism than dogs with normal or low body condition scores, and an association between obesity and increased hyperadrenocorticism risk is recognised in human medicine (Lund et al, 2006, Tiryakioglu et al, 2010. However, these earlier studies reported associations rather than causal relationships and there are clearly other possible non-causal explanations for this association.…”
Section: Discussionmentioning
confidence: 97%
“…Screening studies for obese populations usually revealed a low prevalence of CS except for one study that found a prevalence of 9% (6,31,32,33). Moreover, false-positivity rate was found to be 25%, which resulted in unnecessary further investigations (6).…”
Section: Discussionmentioning
confidence: 99%